A Different Level of Caring: Navigating the Intersections of Perception of Care in Teaching - Donna M. Sayman; Kell Carrero; Mandy E. Lusk (The Advocate, 2018)
This study sought to predict teacher’s perceptions of caring. We surveyed 457 educators using the Caring Abilities Inventory (Nkongho, 1990). Due to the ever increasing diversity of American classrooms, it is critical to determine how to best recognize, recruit, and prepare the next generation of teachers. Findings indicated differences in caring among gender and race. Implications for teacher preparation programs could be a need to gain insight into gendered and racial notions of care.
Keywords: caring; gender and teaching; race and teaching special education; teacher recruitment